VERBAL POLITENESS AND REQUEST STRATEGIES: A COMPARATIVE ANALYSIS OF LEXICAL MEANS IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2026)
This article examines the lexical means employed in verbal politeness and request strategies across English and Uzbek, two typologically distinct languages belonging to different linguistic families. The analysis demonstrates that while both languages possess rich systems of politeness marking, they differ substantially in their morphosyntactic and lexical organization, cultural underpinnings, and the pragmatic weight assigned to specific forms.